Inclusive Education in Asia: Insights From Some Country Case Studies. Issue 1 (22nd November 2020) - Faragher, Rhonda; Chen, Mo; Miranda, Lucena; Poon, Kenneth; Rumiati,; Chang, Feng‐Ru; Chen, Holly
Abstract: Across Asia, countries have signed the UNCRPD and to a greater or lesser extent are pursuing inclusive education (IE). In this article, we present case studies from Singapore, Indonesia, Philippines, and China analyzing them for common themes around the education of students intellectual and developmental disabilities (IDD), and noting commonalities, challenges, and emerging issues. While the definition of IE (being the philosophy, process and practice of welcoming, valuing and supporting all learners in general education environments) and the conceptual distinction between integration and segregation are clear in the UNCRPD and subsequent comments, the terminology used in some of the countries is inconsistent with these definitions. This makes interpretation of reports from government instrumentalities difficult. In some cases, misuse of terminology allows justification of practices that are contrary to the UNCRPD. Terminology differences coupled with challenges of finding data related to the education of children with IDD, if the data exist, make a regional analysis of progress towards IE complex. In our paper, we have drawn on previous reviews and reports to discuss common issues and make suggestions for ways forward. Our findings add to the few other reviews from Asia on IE and draw attention to the continuing need for improved access to any education at all for learners with IDD. Provision of IE is caught up in dilemmas in the region about teacher preparation and professional learning, and how to provide specialist support in inclusive settings. School structure decisions including staffing provision and class sizes affect the education outcomes of students with IDD. School leadership, with the fundamental role of translating policy into practice, is critical for the development of IE and must be aligned with system and country priorities. Collaboration across the region has the potential to share best practice and continue to improve the educational opportunities for learners with IDD.